Local materials for sustainable medium-rise housing: Syria and Ghana - Daoud, Siba; Neizer Kissi, Eugene; Khalil, Ivan (project baikal, 2026)
The article considers the relationship between the concept of sustainable settlement development and the variety of housing development methods. Using the examples of two regions, Syria and Ghana, it shows two main types of “species diversity” of low-rise housing. Syria is characterized by diversity due to the simultaneous presence of elements from various historical eras and cultures, from ancient Egypt and Mesopotamia to modern construction technologies. Ghana is more characterized by a combination of diverse building traditions of differenct peoples inhabiting this multinational region.